(untitled) (Signifiances (Signifying), 2026)
This article defends the thesis of structural monism, according to which all sciences share the same fundamental bipartite structure, analogous to that of human belief. Every belief—and, by extension, every science—comprises two components: a conceptual, non-empirical, and normative component (A), and an empirical, causal, and descriptive component (B). The former defines the categories, norms, or possibilities that render the latter intelligible, while the latter necessarily presupposes the former. On the basis of this distinction, the article examines a wide range of disciplines—linguistics, psychology, physics, chemistry, biology, sociology, evolutionary theory, logic, and philosophy—in order to show that each of them manifests, in different ways, the same structural opposition between conceptual frameworks and empirical phenomena. The author highlights a central asymmetry: it is possible to study component A independently of B, but not vice versa. Particular attention is paid to linguistics, where the langue/parole distinction clearly exemplifies structural monism, as well as to physics and the philosophy of science, especially through the notions of the a priori, theoretical frameworks, and norms of justification.